Leaf trait variability maintains similar leaf exchange rhythms in Hirtella glandulosa Spreng. (Chrysobalanaceae) populations growing on contrasting soil types in the Brazilian Atlantic Forest - de Oliveira, Josevânia Carneiro; dos Santos, Marília Grazielly Mendes; Neves, Sâmia Paula Santos; Vitória, Angela Pierre; Rossatto, Davi Rodrigo [UNESP]; de Miranda, Lia d’Afonsêca Pedreira; Funch, Ligia Silveira (Springer Nature, 2021)
Abiotic and biotic factors constrain species occurrences, although many species are widely distributed. We investigated the performance of two populations of Hirtella glandulosa Spreng. (Chrysobalanaceae), a tropical tree or shrub that occurs from Venezuela to southeastern Brazil. This study was carried out in two evergreen Atlantic Forests fragments in the Chapada Diamantina Mountains (Brazil) growing on sites with different soil types and different water availabilities: a river margin on litholic soils (river/lithosol) and a plateau with the deep clayey soils (plateau/latosol). We examined leaf phenology, water potential (ΨW), wood density, leaf traits, and leaf gas exchange of populations growing at both sites in the rainy and dry seasons. Despite differences in their ΨW values, both populations maintained similar leaf phenological patterns. Leaf traits, ΨW, and leaf gas exchange differed spatially and temporally. The maintenance of phenological strategies conditioned by distinct leaf and gas exchange traits compensated for lower water potential levels in the river margin/lithosol site and favored the maintenance of a positive water balance and greater water use efficiency than in the plateau/latosol site. Morphological and physiological trait adjustments could allow the wide distribution of H. glandulosa in contrasting soil types with different water availabilities.
Keywords: Phenodynamics; Soil properties; Water potential; Wood density